Segregación socioeconómica en las escuelas de Lima Metropolitana (Revista Peruana de Investigación Educativa, 2021)
This study aims to deepen the knowledge of school segregation by socioeconomic status (SES) in the Lima Metropolitan Area. To do this, the magnitude of socioeconomic segregation in schools of this area was estimated by educational level (primary / secondary), type of management (public / private), school fees (private schools), and zoning. The students’ socioeconomic index collected in the 2018 Student Census Assessment was used. The estimation of segregation was carried out through the Dissimilarity Index, the Intraclass Correlation Coefficient, and the Isolation Index. Schools were also categorized by their socioeconomic segregation status.Although the results vary according to the index used, it was found that there is a stronger socioeconomic segregation in primary schools than in secondary schools. Segregation is not a uniform phenomenon, as it varies according to the type of school management. l. While there are strong indications of segregation in both public and private schools, in the latter they are higher for primary and secondary schools. Regarding geographical areas, segregation indices tend to be higher in those that concentrate a greater proportion of students with higher SES. However, students with a lower SES are more likely to coincide with peers of the same socioeconomic status who attend schools in the peripheral districts of the Lima Metropolitan Area. In all the districts analyzed, at least a third of the primary schools and a quarter of the secondary schools are segregated.